Pengaruh Ekstensifikasi Pajak, Sosialisasi Pajak, Dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak (Studi Pada Wajib Pajak Orang Pribadi Di KPP Pratama Jakarta Senen) - Silviana Dwi; Khairur Raziqiin (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The purpose of this research is to find out the effect of tax extensification, socialization, and knowledge on the taxpayer’s compliance (a study on individual taxpayers at Senen Jakarta Small Tax Office). This method adopts the quantitative method, which measures data and statistics objectively through scientific calculations derived from tax extensification, socialization, and knowledge variables in promoting the taxpayer’s compliance. The quantitative approach in this research involves direct and online distribution of questioners to individual tax payers within the area of Senen District, Central Jakarta. Sample are taken using the Slovin’s formula with level of significance 5% or 0,05. The samples used is this research are 100 individual taxpayers. In data processing, SPSS 25 application system is used. The result of this research shows that tax esxtensification, socialization and knowledge have a significant effect on the taxpayer’s compliance.